2017
DOI: 10.1515/ijamh-2017-0027
|View full text |Cite
|
Sign up to set email alerts
|

Trichotillomania in celiac disease patient refractory to iron replacement

Abstract: Trichotillomania is characterized by recurring hair pulling behavior and repeated attempts to decrease or stop the behavior. This behavior can cause a trichobezoar, which is a mass of hair found in the stomach. Patients with diagnosed celiac disease may have an urge to swallow their hair due to iron or folat deficiency, which is called pica. We report a case of an 11-year old girl with celiac disease who has had trichotillomania for a duration of 2 years, and required an operation due to residual gastric hair … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Familial predisposition to mental illness, in addition to stress and socialization factors, must be considered in the detection of symptoms of depression or anxiety. [7,9,10]…”
Section: Discussionmentioning
confidence: 99%
“…Familial predisposition to mental illness, in addition to stress and socialization factors, must be considered in the detection of symptoms of depression or anxiety. [7,9,10]…”
Section: Discussionmentioning
confidence: 99%
“… Trichotillomania improved through gluten-free diet. Kalyoncu et al 9 2017 Trichotillomania was caused by behavioral disorders secondary to celiac disease. Trichobezoar was removed through surgery; gluten-free diet continued.…”
Section: Discussionmentioning
confidence: 99%
“…At that point, she wanted to stop, but she still experienced the cravings she could not resist and continued to swallow her daughter's hair from time to time [ 16 ]. She also contacted her primary care doctor about her unusual behavior, who suggested that vitamin or other nutritional deficiency could also be implicated [ 17 ]. Ms. Z immediately started eating healthier and suppressed her cravings until she managed to completely stop eating her daughter's hair.…”
Section: Case Presentationmentioning
confidence: 99%